Analisis Asuhan Keperawatan Pada Lansia yang Mengalami Instability dengan Resiko Jatuh Menggunakan Intervensi Ergo Care Heel Rise Exercise di Sentra Gau Mabaji Gowa - Aidah Fitriani; Ayu Satriana; Eny Sutria; Patima; Titi Mildawati (Yayasan Ekselensi Daya Indonesia, 2025)
Instability is a balance disorder that is at risk of injury and the risk of falling in the elderly. The ergo care heel rise exercise intervention is one of the treatments that can be given to the elderly at risk of falling. This research analyzes nursing care for the elderly who experience instability and are at risk of falling using the ergo care heel rise exercise intervention at Sentra Gau Mabaji Gowa. The method used is a descriptive approach through the case study method. The subjects in this study were the elderly who experienced instability with a risk of falling. The instruments used in this study were the Morse scale/MFS (Morse Fall Scale) the balance scale and the SOP for giving the ergo care heel rise exercise intervention. Data analysis is presented in textual form various facts presented in text form and explained narratively. The results show that the administration of the ergo care heel rise exercise intervention to the elderly who experienced instability with the risk of falling at the Sentra Gau Mabaji Gowa with successive implementations was carried out for 3 days on March 29-31 2023 and found that the results of the questionnaire before the intervention were on the Morse scale of 75 and the balance value is 7. After the intervention is carried out on the Morse scale of 65 the balance value is 5. It can be concluded that there is an effectiveness of giving the ergo care heel rise exercise intervention to the risk of falling in the elderly. Based on the results of the nursing evaluation in the case, it was stated that giving the ergo care heel rise exercise intervention could improve balance in the elderly who are at risk of falling